The NICA injury surveillance system: Design, methodology and preliminary data of a prospective, longitudinal study of injuries in youth cross country mountain bike racing - Willick, S. E.; Cushman, D. M.; Klatt, J.; Brobeck, M.; Spencer, C.; Teramoto, M. (Journal of Science and Medicine in Sport, 2021)
Objectives: To describe the design and implementation of an injury surveillance system for youth mountain bike racing in the United States, and to report preliminary first-year results. Design: Descriptive sports injury epidemiology study. Methods: After two and a half years of development and extensive beta-testing, an electronic injury surveillance system went live in January, 2018. An automated email is sent to a Designated Reporter on each team, with links to the injury reporting form. Data collected include demographic information, injured body part, injury diagnosis, trail conditions and other factors associated with injury occurrence. Results: 837 unique injuries were reported in 554 injury events among 18,576 student-athletes. The overall injury event proportion was 3.0%. The most common injury among student-athletes was concussion/possible concussion (22.2%), followed by injuries to the wrist and hand (19.0%). Among 8,738 coaches, there were 134 unique injuries reported that occurred in 68 injury events, resulting in an overall injury event proportion of 0.8%. The shoulder (38.2%) was the most commonly injured body part among coaches. Injuries among coaches tended to more frequently result in fractures, dislocations and hospital admission compared with injuries among student-athletes. Among student-athletes, female riders sustained lower limb injuries more than male riders (34.0% vs. 20.7%, p < 0.001). Conclusions: A nationwide injury surveillance system for youth mountain bike racing was successfully implemented in the United States. Overall injury event proportions were relatively low, but many injury events resulted in concussions/possible concussions, fractures, dislocations and 4 weeks or longer of time loss from riding.